Bone Mesenchymal Stem Cell-Derived sEV-Encapsulated Thermosensitive Hydrogels Accelerate Osteogenesis and Angiogenesis by Release of Exosomal miR-21 - Wu, Di; Qin, Hao; Wang, Zixuan; Yu, Mingzhao; Liu, Zhe; Peng, Hao; Liang, Leilei; Zhang, Changqing; Wei, Xiaojuan (Frontiers in Bioengineering and Biotechnology, 2022)
Angiogenesis has been recognized to play an essential role in remodeling new bone (osteogenesis). Exosomes, the endogenously secreted nanovesicles by cells, exhibit great potential in the regeneration of bone defects and the realization of cell-free therapy. Chitosan, a natural polysaccharide, can form a thermosensitive injectable hydrogel through the addition of β-glycerophosphate. Herein, we developed injectable thermosensitive hydrogel-encapsulated exosomes derived from bone mesenchymal stem cells, which significantly prolonged delivery and release and synergistically enhanced bone regeneration. Exosomes were isolated and characterized, and the physicochemical properties, release kinetics, and biocompatibility of the hydrogels were analyzed. In vitro experiments were performed to investigate osteogenic differentiation, cell proliferation and migration, and tube formation. Thereafter, exosomes were added to the chitosan/β-glycerophosphate hydrogel (Exo@CS/β-GP composite) to repair calvarial defects in rats. The results showed that exosome-loaded hydrogels were biocompatible, exhibiting excellent thermosensitive properties and enhancing bone regeneration. Furthermore, mechanistic studies revealed that exosomal miR-21 targeted SPRY2, thereby promoting angiogenesis. Our study provides new insights on the repair of bone defects with multifunctional controlled-exosome-release hydrogels, which shows great potential in the repair of tissues in the future.